The influence of body composition on exercise-associated skin temperature changes after resistance training. (July 2018) - Weigert, Martin; Nitzsche, Nico; Kunert, Felix; Lösch, Christiane; Schulz, Henry
Abstract: Resistance exercise leads to an increase in skin temperature (Tskin ) in the area of the exercised muscle. Infrared thermography seems to be applicable to identify these primary used functional muscles with measuring Tskin changes. The aim of the current study was to investigate the influence of body composition on Tskin patterns after resistance exercise. 38 male subjects (19–32 years, BMI 20.4–55.2 kg/m 2 ) participated. Body fat percentage and biceps skinfold thickness were calculated. The subjects were divided into two groups: lean group (LG) with body fat percentage < 25%, obese group (OG) with body fat percentage ≥ 25%. All participants completed three sets with ten repetitions of unilateral biceps curl at 50% of the one repetition maximum. To represent exercise-induced changes of Tskin to rest (Trest ), the algebraic difference of each time point to Trest was calculated. The resulting delta values (∆) are as follows: immediately after the first, second, and third set (∆Tset1, ∆Tset2, ∆Tset3 ), and at 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30 min after the third set (∆T1 -∆T30 ). The maximum positive difference to Trest was defined as ∆Tmax, and the time to reach ∆Tmax was defined as Time to ∆Tmax . LG and OG differed significantly at Trest (32.8 ± 0.9 vs. 31.1 ± 1.4 °C), ∆Tmax (1.9 ± 0.4 vs. 0.9 ± 0.8 °C), Time to ∆Tmax (4.5 ± 2.0 vs. 17.6 ± 10.2 min) and at ∆Tset2 to ∆T15 (p < 0.005). Correlations between body composition (BMI, body fat percentage, biceps skinfold thickness) and Trest, ∆Tset2, ∆Tset3, ∆Tmax (−0.47 <r < −0.74, p < 0.005) and Time to ∆Tmax (0.52 <r < 0.70, p < 0.005) could be shown. In LG, a homogeneous load-induced Tskin pattern was found in all subjects, whereas heterogeneous Tskin progressions were shown in the OG. In conclusion, a greater body fat percentage and a greater skinfold thickness are associated with delayed and lower increases in Tskin after resistance exercise. In contrast to lean subjects, identifying the primary used functional muscles using infrared thermography in obese subjects is challenging. Highlights: Body composition had an influence on skin temperature changes after resistance exercise. A greater skinfold thickness was associated with delayed and lower increases in skin temperature. Lean men showed homogeneous exercise-induced skin temperature patterns. Obese men showed heterogeneous progressions.